STRATEGI KEPEMIMPINAN DALAM MEWUJUDKAN LINGKUNGAN KERJA YANG INKLUSIF DI UNIVERSITAS BAHAUDIN MUDHARY MADURA. - Halimatus Sa'adah; Moh. Agus Salim (re-JIEM (Research Journal of Islamic Education Management), 2025)
The role of leaders is crucial in the workplace, particularly in creating a safe, comfortable, and prosperous atmosphere for employees. Leaders are required to manage employees inclusively to create positive and productive working relationships. Current research indicates that some leaders still lack a grasp of the inclusive approach, resulting in less harmonious working relationships and a decline in employee motivation and productivity. This study aims to analyze the strategy of leaders in building an inclusive work environment. The research approach uses a descriptive qualitative method with data collection techniques of observation, interviews, and documentation. Data were analyzed through data condensation, data presentation, and conclusion drawing. The results show that inclusive leadership plays a significant role in creating a comfortable work environment through open communication, emotional support, fair role allocation, and employee involvement in decision-making. This condition has been shown to increase employee safety, comfort, motivation, and work productivity. This study provides useful references for leaders and organizations in strengthening inclusive leadership practices in the workplace.